A mulher virgem entre estabilizações e deslocamentos: análise de discursos sobre a virgindade feminina em romances de época e suas fanfictions - Amorim, Aline Oliveira (Universidade Federal de São Carlos, 2025)
This paper aims to reflect on virginity as a topic relevant to gender discussions. To this end, we have narrowed the theme down to discourses produced in “Os Bridgertons” (2013-2016), a collection of eight historical romance novels set in the British regency period, and fan fiction derived from this canonical material. Theoretically affiliated with the theoretical-methodological device of materialist Discourse Analysis (DA), we mobilize the concepts of discursive subject, interdiscourse and intradiscourse, conditions of production, discursive formation, paraphrase, and polysemy. The corpus of analysis covers twelve excerpts in total, six from “Os Bridgertons” (2013-2016) collection and six from fanfiction in English and Portuguese available in digital form on multifandom websites. With this, we aim to investigate the tension between stabilization and displacement, in the books of the collection and in the fanfictions derived from them, of effects of meaning on female virginity sustained by different conditions of production. The theoretical-methodological device of Discourse Analysis enabled us to arrive at the reading that, in the aforementioned corpus, there is a predominance of paraphrastic processes, that is, of stabilization, with regard to the theme of female virginity, as well as the virgin woman and her first sexual intercourse.
The virgin woman between stabilizations and displacements: analysis of discourses on the female virginity in period novels and their fanfictions
Keywords: Análise do discurso; Mulher; Virgindade feminina; Discourse analysis; Woman; Female virginity; LINGUISTICA, LETRAS E ARTES::LINGUISTICA